1980
DOI: 10.1007/bf01866570
|View full text |Cite
|
Sign up to set email alerts
|

Zur Morphinbestimmung in Kopfhaaren

Abstract: Detectable amounts of morphine are apparently deposited in the hair of the head after long-term abuse. In 10 of 20 drug-induced deaths investigated it was possible to determine morphine values between 0.1--1 mg/100 g of hair with the appropriate preparation and application of sensitive, specific techniques. The method is suitable to prove prolonged abuse of morphine or heroin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 5 publications
0
7
0
3
Order By: Relevance
“…2. The detection of the drugs after successive hair washing indicates that the substances were contained within the hair and not on the surface (Goldblum et al 1954;Harrison et al 1974;Klug 1980;Baumgartner et al 1981;Valente et al 1981;Baumgartner et al 1982;Niwaguchi et al 1983;Puschel et al 1983;Suzuki et al 1984).…”
Section: Discussionmentioning
confidence: 96%
“…2. The detection of the drugs after successive hair washing indicates that the substances were contained within the hair and not on the surface (Goldblum et al 1954;Harrison et al 1974;Klug 1980;Baumgartner et al 1981;Valente et al 1981;Baumgartner et al 1982;Niwaguchi et al 1983;Puschel et al 1983;Suzuki et al 1984).…”
Section: Discussionmentioning
confidence: 96%
“…Nearly ten years later Baumgartner et al (5) in the USA and in Europe Klug (16) and Arnold, Püschel et al (2,3,4,(17)(18)(19) first discovered opiates in human hair of the head by means of radioimmunological methods. In the course of further examination -carried out with radioimmunoassays (RIA) -phencyclidine (20), methaqualone (21), cocaine (22) and amphetamine (23) were identified and the results were partly verifled by mass spectrometry and gas chromatography.…”
Section: Hair Analysis For Organic Pharmaceuticalsmentioning
confidence: 99%
“…Baumgartner et al [16], Klug [17] and Nagai et al [7] reported that hair is one of the sties of in vivo deposition of narcotics and stimulants, and that their accumulation is associated with the history of abuse. The transfer of MAMP and AMP into the hair is not known minutely.…”
Section: Discussionmentioning
confidence: 99%